Frontal and temporal lobe contributions to emotional enhancement of memory in behavioral-variant frontotemporal dementia and Alzheimer's disease - Kumfor, Fiona; Irish, Muireann; Hodges, John R.; Piguet, Olivier (Frontiers in Behavioral Neuroscience, 2014)
Emotional events gain special priority in how they are remembered, with emotionally arousing events typically recalled more vividly and with greater confidence than non-emotional events. In dementia, memory and emotion processing are affected to varying degrees, however, whether emotional enhancement of memory for complex ecologically valid events is differentially affected across dementia syndromes remains unclear, with previous studies examining effects of emotion on simple visual recognition only. Here, we examined memory for an emotionally arousing short story and a closely matched, emotionally neutral story in behavioural-variant frontotemporal dementia (bvFTD) (n = 13) and Alzheimer’s disease (AD) (n = 14), and contrasted their performance with healthy controls (n = 12). Multiple-choice recognition memory for specific details of the story was assessed after a 1-hour delay. While AD and control groups showed enhanced memory for the emotional story, the bvFTD group recalled a similar number of details from the emotional and neutral stories. Voxel-based morphometry analyses revealed emotional enhancement of memory correlated with distinct brain regions in each patient group. In AD, emotional enhancement was associated with integrity of the bilateral hippocampus, parahippocampal gyri, temporal fusiform gyrus and frontal pole, regions implicated in memory processes. In contrast in bvFTD, integrity of emotion processing regions, including the orbitofrontal cortex, right amygdala and right insula, correlated with the extent emotion enhanced memory. Our results reveal that integrity of frontal and temporal regions determine the quality and nature of emotional memories. While emotional enhancement of memory is present in mild AD, in bvFTD emotion does not facilitate memory retrieval for complex realistic events. This attenuation of emotional enhancement is due to degradation of emotion processing regions, which may be important for modulating levels of arousal.